Leveraging agriculture for improving nutrition and health: Highlights from an international conference - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
Agricultural development has traditionally focused on raising productivity and maximizing production of cereals. In this regard, the world’s farmers and farming systems have made enormous advances, multiplying cereal production several times over in the past half century. Yet hunger, malnutrition, and poor health remain widespread and persistent problems. Nearly 1 billion people still go hungry, and billions more are malnourished. The food price crisis of 2007–08—and more recent increases in food prices—shows just how vulnerable the global food system is to disruptions related to weather and government policies. At the same time, agriculture faces a number of challenges in the coming decades, including growing population, climate change, water scarcity, land degradation, urbanization and changing diets, rising energy costs, and natural disasters. Looking ahead, agriculture faces the task of contributing to food security, nutrition, and good health for a rising number of people. Can it meet the challenge? In February 2011, about 1,000 people came together at a conference in New Delhi to think through the interactions among agriculture, nutrition, and health and consider ways to exploit them to improve human nutrition and health. Participants helped clarify what is known about the links among the three sectors, what is not known, and where opportunities for leveraging agriculture for nutrition and health may lie. These conference highlights are intended to identify knowledge gaps, inspire new thinking, and stimulate concrete actions to leverage agriculture to improve nutrition and health.